Abdul Ali bin Nasser bin Rahma Al-Hawizi historian: 1000-1075 A.H. / 1584-1664 A.M - Abdul Rahman Karim, Fardous (Al-Adab Journal, 2020)
This research deals with the march of a scientist, a thinker and a great historian of the scholars, thinkers and historians of Iraq in the eleventh century AH in the seventeenth century AD in the field of knowledge fields in which he created and wrote about, his writings have been over thirty, and the subject of history among those topics which emerged in his writings Historical, political, social, economic and cultural conditions that took place in southern Iraq in some periods of the Ottoman era, which prevailed in Iraq and the Arab world for four centuries, but despite the characterization of this rule of destruction and wars and ignorance and backwardness that affected the Arab society and others, The Arab states enjoyed semi-independent administration that allowed them to act in their internal affairs despite their dependence on the Ottoman rule. Among these states was the province of Basra, ruled by the family of Al-Afrasiyab Al-Diri in the eleventh century AH and the mandate of Al-Huweiza in southeastern Iraq, The family of Al-Masha’sha was about three centuries of Hawiye and was wary of its relations with the Safavids and Ottomans. The Arab identity of the governors of Basra and Hawizah is one of the factors of cultural, literary and cultural prosperity. Among the evidence of this cultural, scientific and cultural prosperity is the abundance of schools, libraries, mosques, the role of science and worship, the care of scientists and students of science and the journey to seek knowledge. In the days of Azza and prosperity and Azorh superiority, and was our historian Abdul Ali bin Rahma al-Hawizi spent the first part of his life in his hometown of Huweizah, wakes up from the scientific sources and sips of the literary nectar and Ijals professors and schools and libraries Until he matured his talent and strengthened his property, headed at the beginning of the fourth decade of his life towards Basra and made his journey in which he offered his goods to the visual society and embraced by the governors of the state was one of their entourage and became the author of the state and poet Ether and submitted most of his works in Basra, the right historical literature that we will review in the search Insha’Allah.